1994
DOI: 10.1046/j.1471-4159.1994.63020617.x
|View full text |Cite
|
Sign up to set email alerts
|

Agonist Binding to α2‐Adrenoceptors Is Elevated in the Locus Coeruleus from Victims of Suicide

Abstract: The binding of an agonist, p‐[125I]iodoclonidine, and an antagonist, [3H]yohimbine, to α2‐adrenoceptors was measured autoradiographically in the locus coeruleus from 10 pairs of antidepressant‐free victims of suicide and age‐matched controls. Agonist binding to α2‐adrenoceptors was significantly greater in the locus coeruleus from victims of suicide compared with control subjects. In contrast, antagonist binding to α2‐adrenoceptors in the locus coeruleus did not differ significantly between control and suicide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
1
3

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(71 citation statements)
references
References 40 publications
5
62
1
3
Order By: Relevance
“…Additionally, suicide is not associated with altered benzodiazepine binding to GABA A receptors in the LC. These findings do not provide support for the hypothesis that altered biochemistry in the LC associated with depression and suicide [20,40,42,43,69] results from disrupted GABAergic input to the LC.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Additionally, suicide is not associated with altered benzodiazepine binding to GABA A receptors in the LC. These findings do not provide support for the hypothesis that altered biochemistry in the LC associated with depression and suicide [20,40,42,43,69] results from disrupted GABAergic input to the LC.…”
Section: Discussioncontrasting
confidence: 69%
“…Numerous pathological alterations in the LC from depressed suicide victims have been described [20,40,42,43,69], and many of these are consistent with the hypothesis that depression is associated with a stress-related over-activity of the LC, and a concomitant deficiency of norepinephrine [36]. One possible mediator of an overactive LC could be reduced GABAergic input to this cell group, based on considerable evidence of deficient GABAergic transmission in depression as described above.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Abnormalities that have been observed in the LC from human depressives (Klimek et al, 1997;Ordway et al, 1994aOrdway et al, , 1994bOrdway et al, , 2003Zhu et al, 1999) can be reproduced, in part, by chronic stress or pharmacological depletion of norepinephrine in rats (Cubells et al, 1995;Lee et al, 1983;Melia et al, 1992;Torda et al, 1985;U'Prichard et al, 1979;Wang et al, 1998;Zafar et al, 1997). Given that stress activates the LC in laboratory animals (Pavcovich et al, 1990), that chronic stress depletes norepinephrine in the LC (Weiss and Simson, 1986), and that stress is a common precipitator of depression in humans, it seems possible that depression may be associated with elevated excitatory input to the LC.…”
Section: Role Of Glutamatergic Signaling In Depressionmentioning
confidence: 99%
“…Previous observations reveal that depression is associated with altered concentrations of several noradrenergic proteins in the LC. For example, elevated levels of tyrosine hydroxylase (TH) (Ordway et al, 1994a;Zhu et al, 1999), increased agonist binding to a 2 -adrenergic receptors (Ordway et al, 1994b(Ordway et al, , 2003, and reduced levels of norepinephrine transporters (Klimek et al, 1997) were previously reported in the LC from major depression and in suicide victims. Interestingly, depletion of norepinephrine or repeated stress in rats can increase TH expression, increase binding to a 2 -adrenergic receptors, and/or decrease binding to the norepinephrine transporter (Cubells et al, 1995;Lee et al, 1983;Melia et al, 1992;Torda et al, 1985;U'Prichard et al, 1979;Wang et al, 1998;Zafar et al, 1997).…”
Section: Introductionmentioning
confidence: 95%